Endotoxic shock - Pacheco Romero, José (2015)
25 cases of endotoxic shock occurred at the Hospital between 1971 and 1980. It was presented predisposing causes endometritis in 68 percent of cases, both postpartum, cesarean section and abortion, chorioamnionitis in 20 percent hysterectomy in 2 patients and urinary infection in one. It was essentially medical treatment in 7 cases, including patients who died before being taken to the operating room. Surgical treatment consisted of dilatation and curettage in 4 patients, abdominal hysterectomy at 8, 5 exploratory laparotomy and drainage of abscess in a wall. They killed 14 women (56 percent).